ELECTRONIC NATIONAL AGRICULTURE MARKET (ENAM) AND ITS ROLE IN TRANSFORMING AGRICULTURAL MARKETING: A LITERATURE PERSPECTIVE - Pawar, Siddhesh Sadashiv; Walke, Shrikrishna Gulabrao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Electronic National Agriculture Market (eNAM) is a pan-India electronic trading portal launched by the Government of India to integrate the existing Agricultural Produce Market Committees (APMCs) into a unified national market for agricultural commodities. This platform aims to overcome long-standing challenges in India’s agricultural marketing system, such as price manipulation, limited market access for farmers, and the dominance of intermediaries. By facilitating transparent, competitive bidding and online transactions, eNAM seeks to empower farmers with better price realization and enhanced market reach. This literature-based study reviews the evolution, framework, and functionality of eNAM while critically analyzing its transformative impact on agricultural marketing practices. It explores how eNAM has improved market efficiency, reduced transaction costs, and encouraged inter-state trade of agricultural produce. Additionally, the review highlights the infrastructural, regulatory, and digital literacy barriers that constrain the full-scale adoption of eNAM, especially among smallholder farmers. The study also discusses various policy reforms and capacity-building efforts that can enhance the platform’s inclusivity and sustainability. The findings suggest that while eNAM marks a significant shift toward digital agriculture and market modernization, its success depends on comprehensive reforms in market operations, digital infrastructure, and stakeholder engagement. The literature affirms eNAM’s potential to revolutionize Indian agricultural marketing, provided it is supported by holistic implementation and adaptive policy measures.